1982
DOI: 10.3347/kjp.1982.20.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic trial of praziquantal (Embay 8440; Biltricide®) on the dermal and cerebral human cysticercosis

Abstract: A total of 28 adult cases who were confirmed cysticercosis with or without cerebral involvements were treated with praziquantel at the daily dose of 3 x 25 mg/kg for 3 to 7 consecutive days and was evaluated for tolerance and therapeutic effects in the trials clinically performed.The assessment of drug efficacy of praziquantel in the dermal cysticercosis was made by comparing the numbers of cysticercus nodules and histopathological findings of the biopsied parasites by means of light, scanning and transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…However, in our study, infection rates of cysticercosis were higher in men than in women. Our study agrees to a previous research that showed a higher allotment rate of cysticercosis in men [11].…”
supporting
confidence: 93%
“…However, in our study, infection rates of cysticercosis were higher in men than in women. Our study agrees to a previous research that showed a higher allotment rate of cysticercosis in men [11].…”
supporting
confidence: 93%
“…Although a recent randomized controlled trial demonstrated the benefit of antihelminthic therapy in patients harboring viable cysts within the brain parenchyma, it is thought to increase inflammation because of cyst involution, leading to worsening clinical states, which might accelerate dissemination of other viable cysticerci 9,10. The long term prognosis of neurocysticercosis is still not satisfactory 3,6,10. Our patient had a long history of intracranial NCC with hydrocephalus and meningitis.…”
Section: Discussionmentioning
confidence: 82%
“…At that time, brain magnetic resonance imaging (MRI) revealed mild hydrocephalus and focal meningitis in the left cerebello-pontine and ambient cistern. A enzyme-linked immunosorbent assay of hos cerebrospinal fluid test confirmed cysticercosis,4,5 and the patient completed 2 cycles of oral praziquantel (PZQ; 50 mg/kg per day in 3 divided doses for 14 days)6 and carbamazepine (CMZ; 400 mg per day in 2 divided doses daily) for seizure prophylaxis. He was well until severe headache recurred 10 years later.…”
Section: Case Reportmentioning
confidence: 99%
“…The concomitant application of serological diagnoses [20,21] provided further evidence for the presence of the worm in the brain. Safe and effective chemotherapeutics for the medical treatment of NC were successfully launched [22,23]. Several molecular and cell biological studies have elucidated bioactive molecules of TsM that are crucially involved in the regulation of homeostatic functions [24,25] and the symbiotic protein interactome network of the worm [26].…”
Section: Introductionmentioning
confidence: 99%